Turning Challenges into Opportunities : The Medium Term Health Expenditure Pressure Study in Timor-Leste - Hou, Xiaohui; Asante, Augustine (World Bank, Washington, DC, 2017)
Timor-Leste has achieved significant improvements in the health sector since becoming independent a little over a decade ago. Timor-Leste is undergoing an epidemiology transition as the non-communicable disease burden increases, while infectious disease prevalence remains high. The report aims to: (i) analyze trends in health sector public expenditures (budgets and realized expenditures); (ii) document trends in staffing and training, including their costs; (iii) understand the likely resource envelope available to the health sector over the next five years (from all sources); and (iv) provide options to adjust expenditures, to support key priorities, and improve the efficiency of existing expenditures to create space for key priorities. This report reviews the critical fiscal issues facing the health sector in the medium term, including the key areas demanding fiscal space, and the likely resource envelope from government and donors. The report analyzes past trends in health expenditures (by the government and donors), forecasts future resource availability, and examines implications for the Ministry of Health (MOH) to sustain delivery of quality health services. The report is organized as follows: chapter one gives introduction. Chapter two analyzes human resource development in health by discussing three scenarios for medium term health staff planning. Chapter three examines trends in government health spending by key expenditure areas and discusses the increasingly important role that government spending will play in the health sector. Chapter four analyzes the past trends in donor health financing in Timor-Leste. Chapter five concludes by reviewing four key areas (rising wage bill, pharmaceutical spending, overseas medical transfers, and declining donor spending) that are exerting pressure on health sector financing, and suggests policy recommendations based on the analysis detailed in this report.